2017
DOI: 10.1111/1346-8138.13730
|View full text |Cite
|
Sign up to set email alerts
|

Lack of XAGE‐1b and NY‐ESO‐1 in metastatic lymph nodes may predict the potential survival of stage III melanoma patients

Abstract: The cancer-testis antigens (CTA) are a large family of tumor-associated antigens expressed by a variety of cancer cells and primitive germ cells of the adult testis and placenta. These tumor-restricted expressing patterns suggest that CTA would be ideal targets for tumor-specific immunotherapy. XAGE-1 is a CTA that was originally identified by computer-based screening, and four transcription variants, XAGE-1a, -1b, -1c and -1d, have been characterized to date. Although the presence of XAGE-1 transcripts has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The result of XAGE-1b is compatible with other tumor, which reported that XAGE-1b + group with melanoma showed poorer prognosis [5] . These ndings demonstrate that XAGE-1b may be related to biological events of GC.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The result of XAGE-1b is compatible with other tumor, which reported that XAGE-1b + group with melanoma showed poorer prognosis [5] . These ndings demonstrate that XAGE-1b may be related to biological events of GC.…”
Section: Discussionsupporting
confidence: 83%
“…XAGE-1b is considered as a tumor serological marker which assisted clinical diagnosis [7,14] . Moreover, signi cant dysregulated levels of XAGE-1b were observed in several tumors [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]21] . However, XAGE-1b expression in GC and its role in the prognosis of GC patients remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NY-ESO-1 and XAGE-1B are one of the CTAs, which are a large family of tumor-associated antigens only in germ cells of the testis and placenta ( 12 , 13 ), and in various malignant tumors, such as melanoma ( 14 ), squamous cell carcinoma ( 15 ), non-small cell lung cancer ( 16 ), gastric cancer ( 17 ), hepatocellular carcinoma ( 18 ), breast cancer ( 19 ), ovarian cancer ( 20 ), bladder cancer ( 21 ), prostate cancer ( 22 ), multiple myeloma ( 23 ), synovial sarcoma ( 24 ), and Ewing’s sarcoma ( 25 ). CTAs can be divided into two groups, those that are encoded on the X chromosome (CT-X antigens) and those that are not (non-X CT antigens) ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hepatocellular carcinoma, elevated serum XAGE-1B tends to be associated with a higher recurrence rate, and may be useful as a prognostic biomarker ( 18 ). Similarly, also in melanoma, lack of NY-ESO-1 and XAGE-1B in metastatic lymph nodes prolonged overall survival ( 14 ). CAS has been reported to be positive by immunostaining for MAGEA4 and NY-ESO-1 ( 28 ), which are CTAs, but whether or not XAGE-1 is expressed in CAS and its usefulness as a prognostic factor have not been clarified.…”
Section: Discussionmentioning
confidence: 99%